2011
DOI: 10.1162/jocn.2010.21489
|View full text |Cite
|
Sign up to set email alerts
|

Phonological Neighborhood Effects in Spoken Word Production: An fMRI Study

Abstract: The current study examined the neural systems underlying lexically conditioned phonetic variation in spoken word production. Participants were asked to read aloud singly presented words which either had a voiced minimal pair (MP) neighbor (e.g. cape) or lacked a minimal pair (NMP) neighbor (e.g. cake). The voiced neighbor never appeared in the stimulus set. Behavioral results showed longer voice-onset time for MP target words, replicating earlier behavioral results (Baese-Berk & Goldrick, 2009). fMRI results r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
80
1
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(92 citation statements)
references
References 52 publications
8
80
1
3
Order By: Relevance
“…For instance, simultaneous activation of two competing phonological representations may give rise to intermediate phonetic realization, as seen for instance in speech errors (Goldrick & Blumstein, 2006;McMillan & Corley, 2010). Baese-Berk & Goldrick (2009) and Peramunage et al (2011) extend this idea to situations of lexical competition which might simultaneously activate different phonological categories, resulting in phonetic gradience.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, simultaneous activation of two competing phonological representations may give rise to intermediate phonetic realization, as seen for instance in speech errors (Goldrick & Blumstein, 2006;McMillan & Corley, 2010). Baese-Berk & Goldrick (2009) and Peramunage et al (2011) extend this idea to situations of lexical competition which might simultaneously activate different phonological categories, resulting in phonetic gradience.…”
Section: Discussionmentioning
confidence: 99%
“…Baese-Berk and Goldrick (2009) [see also Peramunage et al (2011)] argued that initial minimal pair neighbors lead to stronger activation of the target word, leading to an enhancement of the voicing contrast. To account for the current results, final minimal pair neighbors would have to lead to reduced activation of the target word.…”
Section: Discussionmentioning
confidence: 99%
“…2 Voiceless stops in words with a minimal pair neighbor (cod with minimal pair god) are produced with longer voice onset times (VOTs) than stops in matched words without minimal pairs (cop with no minimal pair gop) (Baese-Berk and Goldrick, 2009;Peramunage et al, 2011). As voiceless stops have longer VOTs than voiced stops, this enhances the contrast between initial voiced and voiceless stops.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Kurumada and Jaeger (2013) examined the production of optional case markers in Japanese that are sometimes redundant with other grammatical function cues, and found independent contributions of both production difficulty and predictability. Baese-Berk and Goldrick (2009), with replications using different methodology by Peramunage, Blumstein, Myers, Goldrick, and Baese-Berk (2011), Kirov and Wilson (2012), Buz, Jaeger, and Tanenhaus (2014), looked at voice-onset time (VOT), an important cue to voicing contrasts in English stops. They found that talkers produce a stronger VOT contrast when both words of a voicing minimal pair have plausible referents in the current discourse context.…”
Section: Introductionmentioning
confidence: 99%